Biax experiment data - Zoet, Lucas (AGU, 2020)
While analysis of glacial seismicity continues to be a widely-used method for interpreting subglacial processes, the underlying mechanics controlling basal stick-slip seismicity remain speculative. Here, we report on laboratory shear experiments of debris-laden ice over a bedrock asperity under carefully controlled conditions. By modifying the elastic loading stiffness we generated a range of stick-slip events. Our work represents the first comprehensive lab observations of unstable ice-slip events (icequakes), and replicates several seismological field observations of glacier slip, such as slip velocity, stress drop, and the relationship between stress drop and recurrence interval. We also observe that stick-slips initiate above a critical driving velocity, and that stress drop magnitude decreases with further increases in velocity, consistent with friction theory and rock-on-rock friction laboratory experiments. Our results demonstrate that glacier slip behavior can be accurately predicted by the constitutive rate-and-state friction laws that were developed for rock friction.
This data is experimental data from the biax device at Penn State
Keywords: glacier slip